Pemanfaatan Obat Tradisional Lancau Wolio Dalam Menjaga Status Kesehatan Lansia di Masa Pandemi Covid 19 di Kota Baubau - Anita Anita; Sri Ernawati; Syastriyani Isna Putri Syarif (Jurnal Ners, 2025)
Basic Health Research data from the Ministry of Health in 2018 shows that the most diseases in the elderly are non-communicable diseases such as heart disease, diabetes, stroke, rheumatism, and injury. Along with the decline in the immune system, the elderly are also a group susceptible to infectious diseases such as respiratory infections, diarrhea, and pneumonia. This is the reason why elderly people are susceptible to various diseases, including COVID-19 which is caused by the Sars-Cov-2 virus. Lancau Wolio traditional ingredients have been used for generations by the Buton people. The traditional Lancau Wolio herb is made by utilizing tubers, stems, and roots from 40 types of plants. The purpose of the study was to determine the use of Lancau Wolio Traditional Medicine in Maintaining the Health Status of the Elderly During the COVID 19 Pandemic. This type of research was experimental design with a pretest-posttest design with control group. The sample in this study was 40 elderly people who were divided into 2 groups, the elderly intervention group who consumed Lancau Wolio and the elderly control group who did not consume Lancau Wolio. The intervention was carried out for 2 weeks. Analysis of the data using the Meann-Whitney test. The results showed that there was a difference in blood pressure between the two groups after 2 weeks of treatment, while for blood sugar (diabetes mellitus) there was a decrease in blood sugar levels in each group, but the difference between the two groups showed that the intervention group had a higher r value than the control group. namely 63.4, and the value of p < 0.05. It is hoped that this research can make traditional lancau wolio medicine as an alternative in preventing the transmission of COVID-19 in the elderly by maintaining the health quality of the elderly. Keywords: Lancau Wolio; elderly; Health Status; COVID-19